2004
DOI: 10.1177/154405910408300219
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acculturation on Objective Measures of Oral Health in Haitian Immigrants in New York City

Abstract: Acculturation is a complex phenomenon that can serve as a proxy for cultural norms and behaviors affecting care-seeking, prevention behaviors, and, ultimately, health outcomes. The purpose of this study was to assess the effect of acculturation on the oral health of Haitian immigrants in New York City. We hypothesized that acculturation would be a predictor of the oral health status of the participating individuals. An acculturation scale was specifically developed and validated for this study. A sample of 425… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(63 citation statements)
references
References 14 publications
2
60
0
1
Order By: Relevance
“…The authors observed that immigrants with a lower acculturation level tend to have a less favourable oral health compared to those with a higher acculturation level. Ismail and Szpunar (1990), as well as Cruz et al (2004), found similar results when studying the impact of acculturation on the oral health of Mexican and Haitian immigrants in the USA. In our present case, we can assume that Turkish families (mainly represented in Group M1) have generally a lower acculturation level compared to Russian families (mainly represented in Group M2) who have generally an initial life style similar to that of the Germans.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…The authors observed that immigrants with a lower acculturation level tend to have a less favourable oral health compared to those with a higher acculturation level. Ismail and Szpunar (1990), as well as Cruz et al (2004), found similar results when studying the impact of acculturation on the oral health of Mexican and Haitian immigrants in the USA. In our present case, we can assume that Turkish families (mainly represented in Group M1) have generally a lower acculturation level compared to Russian families (mainly represented in Group M2) who have generally an initial life style similar to that of the Germans.…”
Section: Discussionsupporting
confidence: 59%
“…In fact, earlier studies carried out in other western countries have reported a poorer oral health status in children and adolescents of ethnic minorities and immigrants living in these industrialized countries compared to the oral health of the national population. Many of these studies were performed in Sweden (Ekman 1990;Wendt & Jonsell 1996;Källestål & Wall 2002), in Denmark (Petersen 1996;Sundby & Petersen 2003), in Great Britain (Laher 1990;Bedi 1991;Todd & Gelbier 1991), in the USA (Ismail & Szpunar 1990;Nurko et al 1998;Cruz et al 2004) and in Australia (Durward & Wright 1989;Marino et al 2001). In Germany, in spite of the large number of immigrants and the dissimilarity in their origins compared with the other host countries, the oral health of migrant and foreign children has not been evaluated adequately.…”
mentioning
confidence: 99%
“…CATPCA is only a technical solution to combine information, but the validity of the obtained score depends on the quality of the obtained information. While we were not able to study validity of the score in our study, one possibility would be to compare it against subjective self-assessment of acculturation or instruments measuring cultural preferences 24 .…”
Section: Less Acculturated Migrantsmentioning
confidence: 99%
“…564 Language barriers reduce access to services and quality of care. 565 Experiential influences (fear of dentists, history of inadequate care, embarrassment about oral condition) are likely hindrances for individuals who require professional dental care. Financial barriers decrease access to dental care.…”
Section: Clinical Considerationsmentioning
confidence: 99%